2014
DOI: 10.1021/cg501464m
|View full text |Cite
|
Sign up to set email alerts
|

Trimorphism of Betamethasone Valerate: Preparation, Crystal Structures, and Thermodynamic Relations

Abstract: The glucocorticoide bethamethasone valerate was investigated for polymorphism. The commercially available modification (Form I) and one methanol solvate were characterized by single crystal structure analysis. DTA-TG and DSC investigations reveal that on solvent removal the methanol solvate decomposes into a new polymorphic modification (Form III), which, upon further heating, transforms into another modification (Form II) via melting and recrystallization. The crystal structures of forms II and III were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…According to the heat of fusion rule [27], it was demonstrated that Form I is the most thermodynamically-stable polymorph. Based on the relevant thermodynamic data and phenomenon, Form I and Form II are in monotropic system [28]; thus, the transformation from Form II to Form I should proceed spontaneously. The stability experiments of the six famoxadone polymorphs are shown in Figures S2-S4.…”
Section: The Characterization Of Starting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the heat of fusion rule [27], it was demonstrated that Form I is the most thermodynamically-stable polymorph. Based on the relevant thermodynamic data and phenomenon, Form I and Form II are in monotropic system [28]; thus, the transformation from Form II to Form I should proceed spontaneously. The stability experiments of the six famoxadone polymorphs are shown in Figures S2-S4.…”
Section: The Characterization Of Starting Materialsmentioning
confidence: 99%
“…phenomenon, Form I and Form II are in monotropic system [28]; thus, the transformation from Form II to Form I should proceed spontaneously. The stability experiments of the six famoxadone polymorphs are shown in Figures S2-S4.…”
Section: The Characterization Of Starting Materialsmentioning
confidence: 99%
“…8 Thus, investigating the polymorphism of APIs is crucial and has practical utility in pharmaceutical research and development. 9,10 Solvates, the crystal forms of a compound that differ in the species or stoichiometry of the included solvent molecules, are widely applied in the pharmaceutical industry. 10 Accidental solvate formation is undesirable during drug processing because of potentially uncontrollable changes in the physicochemical properties of the drug product.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Solvates, the crystal forms of a compound that differ in the species or stoichiometry of the included solvent molecules, are widely applied in the pharmaceutical industry. 10 Accidental solvate formation is undesirable during drug processing because of potentially uncontrollable changes in the physicochemical properties of the drug product. 11 Conversely, solvates with pharmaceutically relevant solvents may improve the physicochemical properties of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In some cases these may be difficult tasks, and much effort, involving a variety of physico-chemical investigations, may be needed to establish all the thermodynamic relationships and to construct the energy-temperature diagram. [13][14][15][16] The energy difference between polymorphic modifications is usually small, but may be large enough to allow for different conformations and/or to redistribute weak intermolecular interactions, thus generating a different packing. 1,4 This might well be the case for solid state structures of polybrominated aromatic systems, in which we are interested particularly with respect to their intermolecular bromine-bromine interactions.…”
Section: Introductionmentioning
confidence: 99%